PENGARUH STORE IMAGE, STORE ATMOSPHERICS, DAN STORE THEATRICS TERHADAP PURCHASE INTENTION PADA THE BODY SHOP GALAXY MALL SURABAYA - Wijaya, Christian Hadi (Kajian Ilmiah Mahasiswa Manajemen, 2013)
We already know that retail development in Indonesia is very rapid. With a burgeoning retail development, making retail business owners must be able to anticipate the competition.Research conducted aimed to determine the effect of store image, store atmospherics and store theatrics on purchase intention at The Body Shop Galaxy Mall Surabaya. This study uses multiple linear regression method. Sampling technique in this study using purposive sampling. This study used a sample of 100 respondents. Characteristics of the sample to know and understand've been on The Body Shop Galaxy Mall Surabaya.The results showed that store image positive effect on purchase intention. Store atmospherics positive effect on purchase intention. Store Theatrics positive effect on purchase intention.